Manual de funciones para Mundoffice C. Ltda. del cantón Quevedo, provincia de Los Ríos, año 2011 - Pérez Luna, Elena Rosaura (2012)
This thesis is carried out at the premises of Mundoffice C. Ltda., located in the Calle Bolívar No. 705 and 7th of the Canton in Quevedo, province of Los Ríos. To achieve this goal had to identify the jobs, which makes up the organizational structure of the CIA, human talent functions were classified depending on the identified areas and hierarchical levels, lines of authority and responsibility, required by the company. Within the methodology for developing manual functions was taken into account the following points: establish the objectives of the company; Formulating objectives, policy and support schemes; Identify and clarify the activities required to achieve them; Grouped these activities in accordance with the human and material resources available, and how best to use them, depending on the circumstances and delegated the necessary authority to carry out activities at the head of each group. To develop the study used two types of research; field, implemented at Mundoffice C. Ltda., using the techniques of observation, surveys and interviews aimed at personnel from the different areas of the company; bibliographic type - documentary, based on texts, books and the internet, based on the object of study. Also implemented several methods; inductive, deductive and analytic, was allowed to collect primary and secondary information according to the subject. The literary review contributed to the realization of this work, also collaborated with the structure of the manual functions. It was clear to see in various jobs in Mundoffice C. Ltda., company work overload, it is generated by the lack of a manual of functions, also have to be defined in detail the roles and responsibilities of the human talent. The proposed hypothesis was positive, as all of the staff of the company stated that the elaboration of the Manual will make it possible to determine the functions of the human talent that works in different areas. Since there is a need of Mundoffice C. Ltda., in optimizing job performance and organize the human talent, it was necessary to establish a proposed, in showing the design of the manual functions, structured according to the functional organizational structure of the company, which will allow to define the functions of staff in the different areas of the company, motivating him and training so that it can carry out efficiently its activities both administrative and commercial. The study was implemented in order to design a Manual of functions for Mundoffice C. Ltda., for the purpose of optimizing the direction in the development of processes, both in the Administration, as a service to the client. The manual functions was designed it because the company presented an informal organization, negatively affected the operational development of human talent, due to lack of knowledge of the functions, resulting distortions at the time of decision-making at the working level.